Distinct fungal microbiomes of two Thai commercial stingless bee species, Lepidotrigona terminata and Tetragonula pagdeni suggest a possible niche separation in a shared habitat - Castillo, Diana C.; Sinpoo, Chainarong; Phokasem, Patcharin; Yongsawas, Rujipas; Sansupa, Chakriya; Attasopa, Korrawat; Suwannarach, Nakarin; Inwongwan, Sahutchai; Noirungsee, Nuttapol; Disayathanoowat, Terd (Frontiers in Cellular and Infection Microbiology, 2024)
Stingless bees, a social corbiculate bee member, play a crucial role in providing pollination services. Despite their importance, the structure of their microbiome, particularly the fungal communities, remains poorly understood. This study presents an initial characterization of the fungal community associated with two Thai commercial stingless bee species, Lepidotrigona terminata (Smith) and Tetragonula pagdeni (Schwarz) from Chiang Mai, Thailand. Utilizing ITS amplicon sequencing, we identified distinct fungal microbiomes in these two species. Notably, fungi from the phyla Ascomycota, Basidiomycota, Mucoromycota, Mortierellomycota, and Rozellomycota were present. The most dominant genera, which varied significantly between species, included Candida and Starmerella. Additionally, several key enzymes associated with energy metabolism, structural strength, and host defense reactions, such as adenosine triphosphatase, alcohol dehydrogenase, β-glucosidase, chitinase, and peptidylprolyl isomerase, were predicted. Our findings not only augment the limited knowledge of the fungal microbiome in Thai commercial stingless bees but also provide insights for their sustainable management through understanding their microbiome.